Enlarged perivascular spaces are associated with cognitive function in healthy elderly men. Issue 11 (15th October 2004) - MacLullich, A M J; Wardlaw, J M; Ferguson, K J; Starr, J M; Seckl, J R; Deary, I J
Abstract : Objectives: Increased white matter (WM) lesions on magnetic resonance imaging (MRI) are associated with worse cognitive function in older people. Enlarged perivascular spaces (EPVS) commonly coexist with and share some risk factors for WM lesions but are not quantified in published scales. It is not known whether the extent of EPVS is also associated with cognitive function. We tested the hypothesis that more EPVS would be associated with worse cognitive function. Methods: Ninety seven healthy men (65–70 years), not on medications, underwent MRI scanning and comprehensive cognitive testing. EPVS were quantified in both the basal ganglia/centrum semiovale and the hippocampus, and WM lesions were measured. Results: Scores on published WM lesion rating scales intercorrelated highly significantly and positively (ρ = 0.61 to 0.91, p<0.0001). A summary (WML) factor derived from principal components analysis of the WM scales correlated with EPVS in the basal ganglia/centrum semiovale (ρ = 0.48, p<0.0001) but not in the hippocampus. EPVS scores in the basal ganglia/centrum semiovale correlated significantly and negatively with non-verbal reasoning (ρ = −0.21, p = 0.038) and general visuospatial ability (ρ = −0.22, p = 0.032), adjusted for prior intelligence. The WML factor correlated significantly and negatively with visuospatial ability, as previously reported, and showed an unexpected positive correlation with one test of verbal memory (list-learning). Conclusions: These findings suggest that increased EPVS are correlated with worse cognitive function. Future studies examining changes in WM with ageing should consider incorporating measures of EPVS and examine the sequence of EPVS and WM lesion development over time. More work is needed to develop valid and reliable measures of EPVS.